(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Postdated pregnancies are associated with increased perinatal morbidity and mortality. The risk increases when pregnancy continues beyond 41 wks. So, the Induction of labor conducted at or beyond 41 wks could help prevent these complications. But there are certain risks associated with Induction of labor. Again, Induction success varies widely and depends on some modifiable and nonmodifiable factors. Objective: To assess the feto-maternal outcome and analyze the factors affecting the outcome of electively induced labour in postdated pregnancy with a low bishop score compared to spontaneous onset labour in a secondary level hospital. Materials and methods: Prospective analytical study involving 220 participants divided into induction (study) and spontaneous labour (control) groups. Data collected on socio-demographic data, characteristics of the study population, causes of failed Induction, maternal complications and neonatal outcomes. Results: Among electively induced postdated pregnancy (study group) vaginal delivery was 45.45% with caesarean section 54.54% compared to 80% and 20% respectively in the spontaneous labour (control group). Cervical dystocia was the commonest indication for caesarean section (P=0.001). Among maternal complications control group had significant perineal lacerations (P=0.016) and study group had a longer duration of hospital stay (P<0.001). The neonatal outcome didn’t show significant difference. Conclusion: The present study showed routine Induction of labor in prolonged pregnancy may encourage higher caesarean section rate with prolonged hospital stay but judicious Induction even in poor bishop score is not associated with any major feto-maternal complication. Further multicentric study with a larger sample size is recommended. J Bangladesh Coll Phys Surg 2022; 40: 175-182